Perceived Environmental Corporate Social Responsibility and Employees’ Innovative Behavior: A Stimulus–Organism–Response Perspective - Wu, Weiwei; Yu, Li; Li, Haiyan; Zhang, Tianyi (Frontiers in Psychology, 2022)
Drawing from the stimulus-organism-response (S-O-R) model, this study aims to examine how and under what circumstances perceived environmental corporate social responsibility (ECSR) affects employees’ innovative behavior in the context of environmental protection. Using a sample of 398 employees from different firms in high energy-consuming industry of China, the results indicate that, at first, perceived ECSR a positive effect on organizational identification. Secondly, organizational identification has a positive influence on employees’ innovative behavior. Thirdly, organizational identification plays an important mediating effect between perceived ECSR and employees’ innovative behavior. Fourthly, both the effect of perceived ECSR on organizational identification and the indirect effect of perceived ECSR on employees’ innovative behavior via organizational identification will be stronger when the levels of organizational trust are high. These findings add new insights into the perceived ECSR-employees’ innovative behavior relationship and provide important managerial implications for enhancing ECSR perception to improve employees’ innovative behavior.